Composition and Diversity of Avifauna Species in the Angke-Kapuk Protected Forest Area, North Jakarta - Kusumahadi, Khoe Susanto; Husein, Haris Zakian; Hamdani, Moh. (Journal of Tropical Biodiversity, 2024)
Birds are a good indicator for identifying areas rich in biodiversity, including environmental changes and problems. The reduced number of birds also indicates environmental degradation. Birds play an important role in an ecosystem in maintaining biological balance. These roles include pollinating plants, controlling insect populations and playing a role in the dispersal of plant seeds. In fact, several species of birds are considered key species where their presence in an ecosystem can indirectly influence the existence of other species. Birds need a habitat that acts as a source of food, a place to socialize, reproduce, take shelter, rest and nest. The mangrove area in the Angke-Kapuk Muara Angke Protected Forest is an important bird area or Import Bird Area. The method used is the Visual Encounter Survey (VES). Each species of avifauna found at the observation location was recorded and counted. Bird watching is carried out in the morning at 06.30 – 09.30 WIB. Observations are carried out using a transect route, that is, the observer will walk along the existing observation route. This research will be carried out in the Pantai Indah Kapuk area, namely in the Angke-Kapuk Muara Angke Protected Forest, North Jakarta. This research was conducted in November 2023. This research aims to determine the species composition and diversity of avifauna species at Pantai Indah Kapuk, North Jakarta. Based on the results of research conducted at 11 locations in the Pantai Indah Kapuk area, it was found that there were 62 species of birds from 31 families. The highest number of bird species was found in plot 1, namely 44 species belonging to 24 families and plot 9, namely 36 species belonging to 23 families.